2006
DOI: 10.1002/pmic.200500243
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and SAGE profiling of murine melanoma progression indicates the reduction of proteins responsible for ROS degradation

Abstract: Using 2-DE of total cell protein extracts, we compared soluble proteins from murine melanoma lines Tm1 and Tm5 with proteins from the nontumoral cell melan-a from which they were derived. Seventy-one of the 452 spots (average) detected with CBB were differentially accumulated, i.e., increased or decreased twofold. Forty-four spots were identified by PMF/MALDI-TOF, 15 with increased and 29 with decreased protein levels. SAGE showed that 17/34 (50%) of the differentially accumulated proteins, pI range 4-7, prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0
9

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 52 publications
5
36
0
9
Order By: Relevance
“…Melanocytes are particularly sensitive to oxidative stress (7), which is chronically generated during melanogenesis (8) due to the pro-oxidant effect of melanin (9). Melanoma tissues exhibit increased products of lipid peroxidation and levels of antioxidant enzymes compared with benign nevi (10), and oxidative dysregulation is correlated with melanoma progression in a mouse model (11). These observations support the notion that UV-induced oxidative stress/damage contributes to melanoma pathogenesis (12) and could be targeted using antioxidant preventive therapy.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…Melanocytes are particularly sensitive to oxidative stress (7), which is chronically generated during melanogenesis (8) due to the pro-oxidant effect of melanin (9). Melanoma tissues exhibit increased products of lipid peroxidation and levels of antioxidant enzymes compared with benign nevi (10), and oxidative dysregulation is correlated with melanoma progression in a mouse model (11). These observations support the notion that UV-induced oxidative stress/damage contributes to melanoma pathogenesis (12) and could be targeted using antioxidant preventive therapy.…”
supporting
confidence: 71%
“…Thus, overcoming this extreme tendency toward the development of melanocytic tumors would require particularly robust protection. Second, although there is evidence that oxidative stress is pathogenic in the development of melanoma (11,12), there are clearly additional pathways such as oxidation-independent UV-induced DNA damage (indicated by formation of CPDs) that we found were unaffected by NAC. In addition, other UV-induced pathways leading to cell cycle deregulation and modulation of apoptosis resistance may contribute to melanoma in this model and not be amenable to protection by NAC.…”
Section: Discussionmentioning
confidence: 66%
“…PKCb is activated in response to oxidative stress, which is produced by UV radiation and is elevated in melanoma because of oncogene activation (e.g., BRAF) (de Souza et al, 2006;Fried and Arbiser, 2008;Govindarajan et al, 2007;Meyskens et al, 2001;Zaidi et al, 2008). Elevated reactive oxygen species (ROS) are also produced in response to PKCb activation because of the phosphorylation of p66Shc and activation of the mitochondrial permeability pore, resulting in a positive feedback involving PKCb activation and ROS generation (DelCarlo and Loeser, 2006;Giorgio et al, 2005;Pinton et al, 2007;Voris et al, 2010).…”
Section: Tumor Suppressive Protein Kinase C Signalingmentioning
confidence: 99%
“…Among these enzymes, Prx is the most abundant enzyme and is known to be involved in receptor tyrosine kinase-mediated signal transduction (12). Interestingly, it has recently been shown that one of the Prx family members Prx2 (gene loci, PRDX2), which belongs to 2-cys Prx subfamily and reduces the peroxides in the presence of NADPH by coupling with thioredoxin/thioredoxin reductase system, is downregulated in melanoma cell lines and particularly in metastatic malignant types (13,14). However, the function of the Prx2 enzyme in the melanoma cell growth and metastasis remains unknown.…”
Section: Introductionmentioning
confidence: 99%